DAMPAK SUPERVISI DAN PELATIHAN TERENCANA TERHADAP ADAPTASI ORGANISASI MELALUI LEARNING AGILITY DI DINAS PENDIDIKAN PROVINSI SULAWESI SELATAN - Hendra Gunawan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2023)
This study analyzes the impact of supervision and planned training on organizational adaptation through learning agility at the Education Office of South Sulawesi Province. The population refers to human resource data consisting of 27,130 employees and education personnel, with a sample of 100 respondents determined using the Slovin formula at a 10% margin of error. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that supervision has a positive and significant effect on learning agility and organizational adaptation. Planned training also has a positive and significant effect on learning agility and organizational adaptation. Learning agility positively and significantly affects organizational adaptation and mediates the effects of supervision and planned training on organizational adaptation. The R-square values show that the model explains 0.388 of learning agility and 0.517 of organizational adaptation. These findings indicate that organizational adaptation in a public education agency depends not only on formal programs but also on supervision quality, planned learning, and employees' ability to apply new experiences.